Endoscopic versus Open Approach to the Infratemporal Fossa: A Cadaver Study - Youssef, Ahmed (J Neurol Surg B Skull Base, 2015)
Introduction Various lateral and anterior approaches to access the infratemporal fossa (ITF) have been described. We provide our observations regarding the endoscopic transpterygoid and preauricular subtemporal approaches, listing their respective advantages and limitations through cadaveric dissection. Methods A cadaver study was performed on five adult specimens. An endoscopic transpterygoid approach to the ITF was completed bilaterally in three specimens, and an open preauricular ITF approach was performed bilaterally in two specimens. Results After completing the cadaveric dissections, we studied differences between the endoscopic transpterygoid approach and open preauricular subtemporal approaches in regard to exposure and ease of dissection of different structures in the ITF. Conclusions In comparison with a lateral approach, the endonasal endoscopic transpterygoid approach provides better visualization and more direct exposure of median structures such as the nasopharynx, eustachian tube, sella, and clivus. We concluded that the endoscopic transpterygoid approach can be utilized to resect benign lesions and some select group of malignancies involving the infratemporal and middle cranial fossae. Open approaches continue to play an important role, especially in the resection of extensive malignant tumors extending to these regions.